2018
DOI: 10.2174/1874279301810010023
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides Infection in a Man with Abdominal Pain and a History of Rheumatoid Arthritis

Abstract: Background:Strongyloidiasis is self-limited by the complete immune system, it may be complicated and causes hyperinfection in immunocompromised patients. Objective: Here, we report a case of an immunocompromised patient with duodenal involvement ofStrongyloides stercoralis.Case Report:A 65-year-old man presented with severe pain in central abdomen and periumbilical regions. He had no history of alcohol consumption, smoking and surgery but the history of RA (Rheumatoid Arthritis) and hypothyroidism taking immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…a) The authors [9] reported the case of a 65-year-old man with rheumatoid arthritis and duodenal involvement of S. Stercoralis.…”
Section: Opinionmentioning
confidence: 99%
“…a) The authors [9] reported the case of a 65-year-old man with rheumatoid arthritis and duodenal involvement of S. Stercoralis.…”
Section: Opinionmentioning
confidence: 99%